2016
DOI: 10.3390/insects7040052
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Mosquito Vectors: Past, Present, and Future

Abstract: Mosquitoes represent the major arthropod vectors of human disease worldwide transmitting malaria, lymphatic filariasis, and arboviruses such as dengue virus and Zika virus. Unfortunately, no treatment (in the form of vaccines or drugs) is available for most of these diseases and vector control is still the main form of prevention. The limitations of traditional insecticide-based strategies, particularly the development of insecticide resistance, have resulted in significant efforts to develop alternative eco-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
259
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 339 publications
(268 citation statements)
references
References 161 publications
(202 reference statements)
1
259
0
8
Order By: Relevance
“…We then showed that more in-depth study of mosquito ecology and behaviors, which can give us direct information about individual parameters, was more efficient in terms of improving model identifiability. Unfortunately, obtaining accurate measurements for any of these parameters individually can be very difficult in practice, as they often vary depending on environmental and ecological factors such as temperature, weather events such as storms, and predation by other species (Kraemer et al, 2015; Wu et al, 2013; Morrison et al, 2008; Chang et al, 2011; Benelli et al, 2016) We would also need additional information on most of the parameters to make the model fully identifiable, which may not always be feasible. Nevertheless, it is still likely possible to measure the relative magnitude of some parameter subsets (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We then showed that more in-depth study of mosquito ecology and behaviors, which can give us direct information about individual parameters, was more efficient in terms of improving model identifiability. Unfortunately, obtaining accurate measurements for any of these parameters individually can be very difficult in practice, as they often vary depending on environmental and ecological factors such as temperature, weather events such as storms, and predation by other species (Kraemer et al, 2015; Wu et al, 2013; Morrison et al, 2008; Chang et al, 2011; Benelli et al, 2016) We would also need additional information on most of the parameters to make the model fully identifiable, which may not always be feasible. Nevertheless, it is still likely possible to measure the relative magnitude of some parameter subsets (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…[19, 81-85, 126, 127]; see [17] for a review). In this present study, the rice fish, O. melastigma showed high predation rates on the dengue vector A. albopictus 2 nd and 3 rd instar larvae post-treatment with very low doses of AgNP.…”
Section: Impact Of Ag Nanoparticles On Oryzias Melastigma Predationmentioning
confidence: 99%
“…Larvivorous fishes are being successfully exploited for control of mosquito vectors aquatic stages in European, Asian, African and Arabian countries [21,65]. Moreover, the larvivorous fishes provide dual benefits by reducing the mosquito populations and indirectly augmenting the aqua cultural economics [26,73,114,132]; see [17] for a recent review).…”
Section: Introductionmentioning
confidence: 99%
“…Successful transinfections of Wolbachia strains from Drosophila flies to Aedes mosquitoes have resulted in the generation of mosquito lines refractory to arboviruses including ZIKV [43][44][45]. Different mechanisms have been suggested to explain the molecular basis of the pathogen-blocking phenotype: upregulation of immune genes, or production of reactive oxygen species, or competition for limited resources such as cholesterol [46].…”
mentioning
confidence: 99%